Lipid-Laden Macrophages and Inflammation in Atherosclerosis and Cancer: An Integrative View - Lee-Rueckert, Miriam; Lappalainen, Jani; Kovanen, Petri T.; Escola-Gil, Joan Carles (Frontiers in Cardiovascular Medicine, 2022)
Atherosclerotic arterial plaques and malignant solid tumors contain macrophages, which participate in anaerobic metabolism, acidosis, and inflammatory processes inherent in the development of either disease. The tissue-resident macrophage populations originate from precursor cells derived from the yolk sac and from circulating bone marrow-derived monocytes. In the tissues, they differentiate into varying functional phenotypes in response to local microenvironmental stimulation. Broadly categorized, the macrophages are activated to polarize into proinflammatory M1 and anti-inflammatory M2 phenotypes; yet, noticeable plasticity allows them to dynamically shift between several distinct functional subtypes. In atherosclerosis, low-density lipoprotein (LDL)-derived cholesterol accumulates within macrophages as cytoplasmic lipid droplets thereby generating macrophage foam cells, which are involved in all steps of atherosclerosis. The conversion of macrophages into foam cells may suppress the expression of given proinflammatory genes and thereby initiate their transcriptional reprogramming toward an anti-inflammatory phenotype. In this particular sense, foam cell formation can be considered anti-atherogenic. The tumor-associated macrophages (TAMs) may become polarized into anti-tumoral M1 and pro-tumoral M2 phenotypes. Mechanistically, the TAMs can regulate the survival and proliferation of the surrounding cancer cells and participate in various aspects of tumor formation, progression, and metastasis. The TAMs may accumulate lipids, but their type and their specific roles in tumorigenesis are still poorly understood. Here, we discuss how the phenotypic and functional plasticity of macrophages allows their multifunctional response to the distinct microenvironments in developing atherosclerotic lesions and in developing malignant tumors. We also discuss how the inflammatory reactions of the macrophages may influence the development of atherosclerotic plaques and malignant tumors, and highlight the potential therapeutic effects of targeting lipid-laden macrophages in either disease.